Differences in cytokines expression between Vero cells and IPEC-J2 cells infected with porcine epidemic diarrhea virus - Yuan, Chen; Sun, Lidan; Chen, Ligong; Li, Limin; Yao, Zuojun; Wang, Yawen; Guo, Haiyong; Li, Tanqing; Song, Qinye (Frontiers in Microbiology, 2022)
Porcine epidemic diarrhea virus (PEDV) primarily infects suckling piglets and causes severe economic losses to the swine industry. Cytokines, as part of the innate immune response, are important in PEDV infection. The cytokines secreted by cell infection models in vitro might reflect true response to viral infection of target cells in vivo. Vero cells and IPEC-J2 are commonly used as an in vitro model to investigate PEDV infection. However, it is not clear which type of cells is more beneficial to the study of PEDV. In our study, firstly, Vero cells and IPEC-J2 were successfully infected with PEDV virulent strains (HBQY2016) and attenuated vaccine strains (CV777) and were capable of supporting virus replication and progeny release. Moreover, cytokine differences expression by Vero cells and IPEC-J2 cells infected with two PEDV strains were analyzed. Compared with IPEC-J2 cells, only the mRNA levels of TGF-β, MIP-1β and MCP-1 were detected in Vero cells. ELISA assay indicated that compared to the control group, the PEDV-infected group had significantly induced expression levels of IL-1β, MIP-1β, MCP-1, IL-8 and CXCL10 in IPEC-J2 cells, while only secretion level of IL-1β, MIP-1β and IL-8 in Vero cells were higher in PEDV infected group. Finally, cytokines change of piglets infected PEDV-HBQY2016 strains were detected by cDNA microarray, and similar to those of IPEC-J2 cells infected PEDV. Collectively, these data determined that the IPEC-J2 could be more suitable used as a cell model for studying PEDV infection in vitro compared with Vero cells, based on the close approximation of cytokine expression profile to in vivo target cells.